Validation of the 36-item version of the WHO Disability Assessment Schedule 2.0 (WHODAS 2.0) for assessing women's disability and functioning associated with maternal morbidity - Carla Silveira; Mary Angela Parpinelli; Rodolfo Carvalho Pacagnella; Carla Betina Andreucci; Carina Robles Angelini; Elton Carlos Ferreira; José Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective To validate the translation and adaptation to Brazilian Portuguese of 36 items from the World Health Organizaton Disability Assessment Schedule 2.0 (WHODAS 2.0), regarding their content and structure (construct), in a female population after pregnancy. Methods This is a validation of an instrument for the evaluation of disability and functioning and an assessment of its psychometric properties, performed in a tertiary maternity and a referral center specialized in high-risk pregnancies in Brazil. A sample of 638 women in different postpartum periods who had either a normal or a complicated pregnancy was included. The structure was evaluated by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), while the content and relationships among the domains were assessed through Pearson's correlation coefficient. The sociodemographic characteristics were identified, and the mean scores with their standard deviations for the 36 questions of the WHODAS 2.0 were calculated. The internal consistency was evaluated byCronbach's α. Results Cronbach's α was higher than 0.79 for both sets of questons of the questionnaire. The EFA and CFA for the main 32 questions exhibited a total variance of 54.7% (Kaiser-Meyer-Olkin [KMO] measure of sampling adequacy = 0.934; p < 0.001) and 53.47% (KMO = 0.934; p < 0.001) respectively. There was a significant correlation among the 6 domains (r = 0.571-0.876), and a moderate correlation among all domains (r = 0.476-0.694). Conclusion The version of the WHODAS 2.0 instrument adapted to Brazilian Portuguese showed good psychometric properties in this sample, and therefore could be applied to populations of women regarding their reproductive history.